The RELN heterozygous single-nucleotide polymorphism rs362691 increases the prefrontal cortical thickness and modulates systemizing-related autistic tendencies in typically developing children and adolescents - Sato, Hiroki; Abe, Mitsunari; Takeuchi, Hikaru; Tomita, Hiroaki; Kure, Shigeo; Kawashima, Ryuta; Taki, Yasuyuki (Frontiers in Neuroscience, 2025)
Reelin, a glycoprotein, plays an essential role in the development and maturation of neural circuits in the cerebral cortex during embryonic and postnatal stages. Animal and human studies suggest that insufficient reelin signaling due to RELN mutations may alter the functional properties of the prefrontal cortex and contribute to cortical dysplasia in the frontal and temporal lobes. A heterozygous missense mutation in RELN, rs362691 (p. Leu997Val), has been proposed to increase susceptibility to autism spectrum disorder (ASD). Based on the empathizing–systemizing theory, this study examined whether the rs362691 variant affects cortical thickness and modulates autism-related cognitive traits in typically developing children and adolescents. We hypothesized that individuals carrying the heterozygous Val/Leu genotype would exhibit greater prefrontal cortical thickness than those with the Val/Val genotype, and that this morphological difference would correlate with autistic cognitive traits. We also explored potential thickness differences in the frontal and temporal cortices. Our results showed that the heterozygous Val/Leu group did not differ from the Val/Val group in empathizing or systemizing trait scores. However, individuals with the Val/Leu genotype exhibited increased cortical thickness in the medial prefrontal sulci, which correlated with individual differences in systemizing traits. No significant association was observed between cortical thickness and empathizing traits across the whole brain. Additionally, greater cortical thickness was observed in the right superior temporal sulcus (STS), although this morphological difference was not associated with empathizing or systemizing traits. These findings suggest that while the rs362691 variant does not significantly influence autism-related cognitive styles per se, it may alter cortical morphology in prefrontal regions functionally linked to systemizing traits in typically developing individuals. Several methodological limitations in the employed data should be considered. Future studies with larger, age-appropriate cohorts and standardized personality measures will be necessary to validate and extend these findings.